First-principles calculations of magnetic and optical properties of (Mn, Mo) co-doped SnSe2. (1st August 2022) - Lin, Long; Pang, Donglin; Shi, Pei; Su, Linlin; Chen, Zehua; Zhang, Zhanying
Abstract: In this paper, based on density functional theory GGA + U method, the electronic structure, magnetic and optical properties of single Mn, single Mo and (Mn, Mo) co-doped SnSe2 are studied. The calculation results show that the doping of single Mn and single Mo can make the intrinsic SnSe2 magnetic. In addition, five different (Mn, Mo) co-doped configurations are calculated and the ∆ E of the stable ferromagnetic configuration is about −227.6 meV. The stable ferromagnetic configuration is caused by the strong hybridization of the d - p orbitals of Mn, Mo and Se atoms and the formation a Mn:3 d -Se:4 p -Mo:4 d coupling chain. And the absorption intensity of SnSe2 system in visible light is improved by the introduction of doped atoms. Our study shows that introducing appropriate dopants is a feasible method to improve the magnetic and optical properties of intrinsic SnSe2 base.